Development of Motion Graphic as Educational Material for Hotel Promotion Using EPIC Model Testing - Abie Pratama; Dwi Ely Kurniawan (Politeknik Negeri Lhokseumawe, 2021)
Beverly Hotel Batam is a four-star hotel located in the city of Batam. In this case, Motion Graphic became the media information to introduce Beverly Hotel Batam to the public. The Motion Graphic implementation in this video offers to provide interesting information to provide attraction and be easily accepted by the recipient of the information. Motion Graphic in this video will provide Beverly Hotel Batam information, and how to use a website to make online bookings at Beverly Hotel Batam. From this promotional media, it will help staff at Beverly Hotel Batam to no longer have to explain it manually and make Motion as a website promotion media, so that in the future guests who want to stay at the Beverly Hotel Batam can make online reservations easily on a website that is already there is. The resulting video is very effective as a promotional media, based on the EPIC Model analysis which reaches an average value of 4.58 based on a scale of 1-5. Empathy: In this dimension, the respondent's response is reached 4.56. In the evaluation it means very effective as a promotional media, Persuasion: In this dimension, the respondent's response reached 4.50. In the evaluation it means very effective as a promotional media, Impact: In this dimension, the respondent's response reached a value of 4.68. In the evaluation is interpreted as effective as a promotional media, Communication: In this dimension, the respondent's response reached 4.59. In the evaluation, it means very effective as a promotional media. Also, the material expert gives a score of 4.71 in the evaluation it means very effective.